Hambatan Multidimensi Penerimaan Publik terhadap Kendaraan Listrik di Kota Surabaya: Konsensus Ahli melalui Modified Delphi - Lutfi Zulkarnain; Rulli Pratiwi Setiawan (Dinasti Research, 2026)
This study examines the multidimensional barriers to public acceptance of electric vehicles (EVs) in Surabaya City, Indonesia, focusing on the expert consensus reached through the Modified Delphi method. Despite ambitious national electrification targets, EV market penetration in Surabaya remains below 0.1 percent, indicating persistent structural obstacles across the economic, socio-cultural, technological, and regulatory dimensions. This research aims to identify and validate the barrier indicators that hinder public acceptance of private EVs by engaging a panel of 20 experts drawn from five stakeholder categories, namely government regulators, academics, practitioners, the private sector, and civil society, selected through purposive sampling. Data were collected through two rounds of structured Delphi questionnaires using a five-point Likert scale, with consensus determined by a mean score of at least 4.00, an interquartile range (IQR) of at most 1.00, and an agreement level of at least 70 to 75 percent. The first round produced consensus on 12 of 18 proposed indicators, while five sub-variables, namely financing institutions, cost complexity, social perception, charging-infrastructure availability, and national policy support, required refinement before reaching consensus in the second round. The final results confirm that all 18 indicators, grouped into four barrier dimensions, are relevant and valid for explaining the low rate of EV adoption in Surabaya. These findings demonstrate that the barriers to EV acceptance are inherently multidimensional and interrelated, requiring an integrated policy approach that combines affordability schemes, infrastructure expansion, regulatory clarity, and public trust-building rather than isolated interventions